How Do Masters of Public Health Programs Teach Monitoring and Evaluation? - Negandhi, Himanshu; Negandhi, Preeti; Zodpey, Sanjay P.; Kulatilaka, Hemali; Dayal, Radhika; Hart, Lauren J.; Grewe, Marybeth (Frontiers in Public Health, 2017)
Introduction: The health systems in developing countries face challenges because of deficient monitoring and evaluation capacity with respect to their knowledge, skills and practices. Strengthening M&E training in public health education can help overcome the gaps in M&E capacity. There is a need to advance the teaching of monitoring and evaluation as a core element of public health education. Objectives: To review Monitoring and Evaluation (M&E) teaching across Masters of Public Health programs and to identify core competencies for M&E teaching in South Asian context. Materials and Methods: We undertook two activities to understand the Monitoring and Evaluation (M&E) teaching across Masters level programs: 1) Desk review of M&E curriculum and teaching in Masters programs globally; 2) Review of M&E teaching across 10 institutions representing four South Asian countries. Subsequently, we used the findings of these two activities as inputs to identify core competencies for an M&E module through a consultative meeting with the ten South Asian universities. Results: Masters programs are being offered globally in 321 universities of which 88 offered a Masters in Public Health), and M&E was taught in 95 universities. M&E was taught as a part of another module in 49 institutions. The most common duration of M&E teaching was four to five weeks. From the 70 institutes where information on electives was available, M&E was a core module/ part of a core module at 42 universities and an elective at 28 universities. The consultative meeting identified 10 core competencies and draft learning objectives for M&E teaching in Masters programs in South Asia. Conclusions: The desk review showed similarities in M&E course content but variations in course structure and delivery. The core competencies identified during the consultation included basic M&E concepts. The results of the review and the core competencies identified at the consultation are useful resources for institutions interested in refining/ updating M&E curricula in their postgraduate degree programs. Our approach for curriculum development as well as the consensus building experience could also be adapted for use in other situations.